2009
DOI: 10.1016/j.juro.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Urinary Incontinence: Greater Impact on Quality of Life

Abstract: Purpose-We compared the impact of mixed, stress and urge urinary incontinence on quality of life in middle-aged or older women.Materials and Methods-We analyzed cross-sectional data from a population based cohort of 2,109 ethnically diverse middle-aged or older women. Among participants reporting weekly incontinence, clinical type of incontinence was assessed by self-reported questionnaires and disease specific quality of life impact was evaluated using the Incontinence Impact Questionnaire. Multivariable logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 16 publications
7
58
2
13
Order By: Relevance
“…Their findings are consistent with several other studies such as [6,9,14,15,25,29,30]. They found that urinary incontinence has more widespread negative effects on quality of life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Their findings are consistent with several other studies such as [6,9,14,15,25,29,30]. They found that urinary incontinence has more widespread negative effects on quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…There is a misconception that the condition cannot be treated [13,14]. UI is not life threatening [8], does not lead to death [15] but the symptoms often impair the social, physical and psychological well-being of affected individuals [16]. Elderly outpatients describe their experience with incontinence as embarrassing, upsetting, and distressing.…”
Section: Introductionmentioning
confidence: 99%
“…Other American and Norwegian studies had reported MUI to be between 20 and 36% [23,33]. MUI is known to be more 'bothersome' and has a larger impact on QOL than other types of UI [1,7,24]. There is a clear need for more thorough studies to assess the types of UI and how it might impact the QOL of the sufferer.…”
Section: Discussion Prevalence and Types Of Urinary Incontinencementioning
confidence: 99%
“…Caucasian women are reported to suffer more of SUI compared to women of African American and Asian descent. Asian women are reported to suffer more from MUI [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Previous gynecological operations, abdominal hysterectomy, surgical menopause [45][46][47] or urologic surgery [36,44] have all been linked as risk factors to UI.…”
Section: Risk Factors Associated With Urinary Incontinencementioning
confidence: 99%
“…2,3 UI prevalence increases with age, reaching one in three older women. 3 The prevalence of UI in young adults ranges from 20 to 30%, from 30 to 40% in middle-aged women, and from 30 to 50% in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%